Absorption and Photoluminescence in Organic Cavity Qed - Herrera-Urbina, F (American Physical Society, 2017)
Organic microcavities can be engineered to reach exotic quantum regimes of strong and ultrastrong light-matter coupling. However, the microscopic interpretation of their spectroscopic signals can be challenging due to the competition between coherent and dissipative processes involving electrons, vibrations, and cavity photons. We develop here a theoretical framework based on the Holstein-Tavis-Cummings model and a Markovian treatment of dissipation to account for previously unexplained spectroscopic features of organic microcavities consistently. We identify conditions for the formation of dark vibronic polaritons, a class of light-matter excitations that are not visible in absorption but lead to strong photoluminescence lines. We show that photon leakage from dark vibronic polaritons can be responsible for enhancing photoluminescence at the lower polariton frequency, and also can explain the apparent breakdown of reciprocity between absorption and emission in the vicinity of the bare molecular transition frequency. Successful comparison with experimental data demonstrates the applicability of our theory. © 2017 American Physical Society.